Open Conversion After Endovascular Aneurysm Sealing: Technical Features and Clinical Outcomes in 44 Patients. (April 2021) - Zerwes, Sebastian; Kiessling, Johanna; Liebetrau, Dominik; Jakob, Rudolf; Gosslau, Yvonne; Bruijnen, Hans-Kees; Hyhlik-Duerr, Alexander
Purpose: To evaluate the technical features and clinical results after open conversion for complications following endovascular aneurysm sealing (EVAS). Materials and Methods: From July 2013 to February 2020, 44 patients (mean age 72±8 years; 36 men) underwent an open conversion due to EVAS complications in a single center. Data were collected on patient characteristics, reasons for conversion, characteristics and duration of the procedure, condition of the polymer, blood loss, time in the intensive care unit (ICU), and intra/postoperative complications. The main outcome measure was mortality at 30 days and in follow-up. Data are presented as the median (IQR) and absolute range. Results: On average, the open conversion took place 3 years after the initial EVAS implantation [median 37 months (IQR 23, 50); range 0–64]. Most patients were converted due migration (82%), aneurysm growth (77%), and/or endoleak (75%), with 21 patients (48%) having all 3 events. Less frequent diagnoses were aneurysm rupture (n=7), aortic infection (n=3), technical failure during implantation (n=2), and graft thrombosis (n=1). The majority of patients (n=26) were asymptomatic and converted electively, but 9 were operated on urgently and 9 emergently (7 late rupture and 2 due to technical failure). The median procedure duration was 178 minutes (IQR 149, 223; range 87–417), the median blood loss was 1100 mL (IQR 600, 2600; range 300–5000). Polymer degradation was mentioned in the operative reports of 18 cases (41%). Patients stayed a median of 3 days (IQR 2, 7; range 1–35) in the ICU, while the median length of stay in the hospital was 14 days (IQR 10, 20; range 0–93). The 30-day mortality was 23% (n=10). During a median follow-up of 3 months (IQR 0, 11; range 0–38), no additional deaths occurred, but 12 patients suffered from an adverse event. There were 3 cases of wound dehiscence after laparotomy, 2 cases of leg ischemia, 2 cases of renal failure, and individual cases of urinary obstruction, urinoma, paralytic ileus, gastrointestinal bleeding, and postoperative delirium. A non-elective setting was associated with a significantly increased mortality of 33% in urgent cases and 56% in emergent cases (p=0.007). Based on these results an algorithm for the management of EVAS complications was developed. Conclusion: The significantly increased mortality associated with nonelective conversions highlights the need for active surveillance. The presented algorithm offers a structured tool to avoid emergency conversions.